How do various leadership practices affect professional learning communities? The mediating role of principals’ perceived trust by teachers - Xiaobo Gu; Zhihui Liu; Zhenyuan Hang (PLoS ONE, 2025)
Drawing on social exchange theory, this study aims to explore the effects of various leadership practices on professional learning communities (PLCs) and the mediating role of principals’ perceived trust by teachers in the relationships between various leadership practices and PLCs from Chinese principals’ perspective. Survey data were collected from 739 principals from different provinces. To examine the proposed model, the study utilized four-step hierarchical regression, Shapley value decomposition, and bootstrap methods. The results indicated that all the four components of leadership practices, namely setting directions, developing people, redesigning the organization and managing the instructional programme significantly and positively affected PLCs, and their contribution rates were 15.81%, 23.43%, 36.48% and 23.25% respectively. Principals’ perceived trust by teachers was a significant mediator between all the four components of leadership practices and PLCs. The practical implications of the findings and suggestions for future research are discussed.